Pemberlakuan Kewenangan Tindakan Menembak Ditempat oleh Aparat Kepolisian dari Perspekif Hak Asasi Manusia - Panjalu, Tri Bagus; Mardjiono, H. R Adianto (Media Hukum Indonesia (MHI), 2024)
This study also aims to analyze the authority of on-site shooting actions carried out by Indonesian police officers from the perspective of Human Rights (HAM). While these actions are also permitted by existing regulations to maintain security and order, this poses a dilemma regarding potential human rights violations. This study uses normative juridical methods with legislative and conceptual approaches, to assess the application of the authority to shoot and its impact on human rights. The purpose of this study is to provide recommendations for appropriate procedures in the use of the authority to fire, which is in accordance with the principles of proportionality and protection of human rights. On-site shooting should only be carried out in emergency situations, after nonviolent efforts have failed, and must meet the principles of legality, necessity, proportionality, and accountability. While these actions are legally valid, challenges such as abuse of authority, lack of transparency, and the risk of misjudgment remain important issues that need to be monitored. Therefore, this study emphasizes the importance of police professionalism in maintaining a balance between law enforcement and human rights protection.